Understanding heterogeneity in social anxiety disorder: Dependency and self‐criticism moderate fear responses to interpersonal cues. (17th October 2013) - Kopala‐Sibley, Daniel C.; Zuroff, David C.; Russell, Jennifer J.; Moskowitz, D. S.
<x xml:space="preserve">Abstract</x> Objective This study examined how the personality traits of self‐criticism and dependency moderated the effects of situational interpersonal cues on fear during interpersonal interactions among individuals with social anxiety disorder (SAD). We hypothesized that self‐criticism would moderate the fear‐inducing effects of situational self‐consciousness and that dependency would moderate the fear‐inducing effects of situational emotional insecurity. Methods Forty SAD patients (Mage = 29.23) and matched community controls (Mage = 28.93) completed event‐contingent record forms after each significant social interaction of over 5 min for a 20‐day period. There were 20 female patients and 20 male patients in each group. Results Event‐level self‐consciousness was more strongly associated with elevations in fear among socially anxious patients who reported higher levels of self‐criticism, while event‐level emotional security was more strongly associated with decreases in fear among SAD patients who reported higher levels of dependency. These interactions were not found in the community sample. Conclusions Findings support the application of personality‐vulnerability models to understanding fear during social interactions in patients with SAD. Results also have implications for psychotherapeutic treatments of SAD. Practitioner points Although social anxiety disorder (SAD) patients are on average more self‐critical and dependent than community participants, some SAD patients are particularly self‐critical, while others are particularly dependent. Highly self‐critical SAD patients are more likely to feel fear during interpersonal situations when they feel self‐conscious. Highly dependent SAD patients are more likely to feel fear during interpersonal interactions when they feel less emotionally secure. SAD patients were compared to a community sample, so we do not know if group differences are due to the presence of SAD or psychopathology in general.